2017
DOI: 10.9789/2175-5361.2017.v9i2.401-407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e Perfil de mulheres grávidas que sofreram violência física Prevalence and profile of pregnant women who suffered physical violence

Abstract: Objetivo: identificar a prevalência e o perfil de mulheres grávidas vítimas de violência física. Métodos: estudo epidemiológico, descritivo, do tipo seccional, realizado com 105 gestantes acompanhadas em quatro Unidades de Saúde da Família do município de Jequié/BA. A coleta de dados ocorreu por meio dos questionários de Abuse Assessment Screen (AAS), Tolerance, Annoyed, Cut down e Eyeopener (T-ACE) e sociodemográfico, sendo analisados no programa SPSS 15.0. Resultados: a prevalência de mulheres grávidas que s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the study, it was determined that pregnant women whose spouses drink alcohol are exposed to more physical abuse. The frequency of consuming two or more drinks per week by the spouse increases the possibility of psychological, physical and sexual abuse against pregnant women (Santos et al, 2017). As intoxication frequency increases, the aggression levels of individuals, causes misunderstanding of verbal or non-verbal cues and increases risk-taking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, it was determined that pregnant women whose spouses drink alcohol are exposed to more physical abuse. The frequency of consuming two or more drinks per week by the spouse increases the possibility of psychological, physical and sexual abuse against pregnant women (Santos et al, 2017). As intoxication frequency increases, the aggression levels of individuals, causes misunderstanding of verbal or non-verbal cues and increases risk-taking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, it was determined that pregnant women whose spouses/partners use drugs are also exposed to more physical abuse. One study found that partner drug use more than doubled the likelihood of perpetrating physical and sexual abuse against pregnant women (Santos et al, 2017). Studies conducted in T€ urkiye have also determined that women whose husbands/partners consume alcohol are more exposed to physical abuse (Akar et al, 2010;Bag˘cıog˘lu et al, 2014;Tokuc x et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation